Optimal Placement and Sizing of Distributed Generators Based on Multiobjective Particle Swarm Optimization - Yang, Deyu; Jia, Junqing; Wu, Wenli; Cai, Wenchao; An, Dong; Luo, Ke; Yang, Bo (Frontiers in Energy Research, 2021)
To solve the problems of environmental pollution and energy consumption, the development of renewable energy sources becomes the top priority of current energy transformation. Therefore, distributed power generation has received extensive attention from engineers and researchers. However, the output of DG is generally random and intermittent, which will cause various degrees of impact on the safe and stable operation of power system when connected to different locations, different capacities, and different types of power grids. Thus, the impact of sizing, type, and location all need to be carefully considered when choosing the optimal DG connection scheme to ensure the overall operation safety, stability, reliability, and efficiency of power grid. This work proposes a distinctive objective function that comprehensively considers power loss, voltage profile, pollution emissions and DG costs, which is then solved by the multi-objective particle swarm optimization (MOPSO). Finally, the effectiveness and feasibility of the proposed algorithm is verified based on the IEEE 33-bus distribution network.